Upacara Ngusabha Yeh di Desa Pakraman Bayung Gede, Kecamatan Kintamani, Kabupaten Bangli (Kajian Teo-Ekologis) - Anak Agung Ayu Alit Widyawati; Mery Ambarnuari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Bali has various rituals in the form of Yaja, all of which are imbued with Hindu religiosity. The lives of rural communities in Bali are completely dependent on nature, and the interpolation of the concept of Hindu teachings in harmony with nature gives rise to the form of Yajña rituals that respect nature. One of the Yajña rituals that have a tendency to preserve nature that will be studied in this article, namely Ngusabha Yeh in Pakraman Bayung Gede Village, Kintamani District, Bangli Regency. The method used in this study is a qualitative descriptive method with primary data sources in the form of interviews and secondary data sources in the form of related literature. This study will discuss the form, function and meaning of the Ngusabha Yeh ceremony in Pakraman Bayung Gede Village, Kintamani District, Bangli Regency. This ceremony serves to awaken the religious side of the people of Pakraman Bayung Gede Village and increase the sense of solidity among the people of Pakraman Bayung Gede Village. The Theo-Ecological meanings that can be found include; God in this case is worshiped as the giver of fertility and the giver of blessings to society.